Mpox outbreak: South Asia needs caution not fear - Mobashwer Ahmed (Knowledge Dynamics, 2024)
The re-emergence of Mpox (formerly monkeypox) has prompted global concern, including in South Asia where cases have surfaced in Pakistan and India. Mpox is a zoonotic virus, primarily spread through direct contact and respiratory droplets, with the 2022 outbreak notably linked to sexual transmission among men who have sex with men (MSM). In August 2024, the World Health Organization declared Mpox a Public Health Emergency of International Concern (PHEIC), urging heightened vigilance. This commentary emphasizes the importance of strengthening disease surveillance at ports of entry, raising public awareness, and targeting high-risk groups, including MSM and HIV-positive individuals. South Asia must also balance its Mpox response with other healthcare priorities. Regional collaboration through SAARC and leveraging local pharmaceutical capacities can enhance preparedness, minimizing the outbreak's impact.